Assessment of the Environmental Sustainability of a Treatment Aimed at Soil Reuse in a Brownfield Regeneration Context. (4th September 2017) - Capobianco, Oriana; Costa, Giulia; Baciocchi, Renato
Summary: A combined stabilization/solidification (S/S) and granulation treatment was shown to be effective, at lab scale, to produce secondary aggregates from a Brownfield soil slightly contaminated by metals. This treatment, as opposed to the frequently adopted "dig and dump" option, allows to combine soil management with site regeneration, minimizing landfill disposal. But is this treatment actually more environmentally sustainable than excavated soil management by dig and dump? To answer this question, we analyzed and compared by life cycle assessment the environmental impacts resulting from the application of the above‐mentioned treatment versus dig and dump on the basis of the results of lab tests performed on a Brownfield soil sample, including leaching test results. The impacts related to the production of all the reagents used in the on‐site treatment, as well as the avoided impacts due to the replacement of raw aggregates with recycled ones, were included. Results showed that the proposed S/S‐granulation process may allow a drastic decrease of the impacts related to land use and resource depletion in comparison to dig and dump, with beneficial effects also with regard to toxicity‐related impact categories. Conversely, the proposed treatment yielded higher impacts, in terms of acidification, water resource depletion, and, in particular, climate change, almost entirely related to the manufacturing of the cement employed for stabilization. However, an average 40% reduction of overall impacts was noted when fly ash cement was assumed to be used as binder instead of Portland cement.